Chronic Pain in Canada - Prevalence, Treatment, Impact and the Role of Opioid Analgesia - Dwight E Moulin; Alexander J Clark; Mark Speechley; Patricia K Morley-Forster (Pain Research and Management)
OBJECTIVE: To assess the prevalence, treatment and impact of chronic pain in Canada.